Assessing the Contributions of Inactivation, Removal, and Transfer of Ebola Virus and Vesicular Stomatitis Virus by Disinfectant Pre-soaked Wipes - Todd A. Cutts; Todd A. Cutts; Catherine Robertson; Catherine Robertson; Steven S. Theriault; Raymond W. Nims; Samantha B. Kasloff; Samantha B. Kasloff; Joseph R. Rubino; M. Khalid Ijaz; M. Khalid Ijaz (Frontiers Media S.A., 2020)
Disinfectant pre-soaked wipes (DPW) containing activated hydrogen peroxide (AHP) or quaternary ammonium compounds (QAC) were tested using ASTM E2967-15 to determine removal, transfer, and inactivation of Ebola virus Makona variant (EBOV/Mak) and vesicular stomatitis virus (VSV) from contaminated stainless steel prototypic environmental surfaces. The infectious virus-contaminated carriers were subjected to wiping in the Wiperator per the standard. Following the use of negative control (J-Cloth)-, AHP-, or QAC-based wipes, recovery of residual infectious virus was assayed. In the case of the J-Cloth wipes (negative control), although removal of virus from inoculated carriers was extensive i.e., ~99% (1.9-3.5 log10) transfer of virus by these wipes to a secondary surface amounted to ≤ 2% (~3.8 log10) of the initial virus load. In the case of each DPW, >6 log10 removal/inactivation of virus was observed, with limited (EBOV/Mak) or no (VSV) virus transfer observed. The efficacy of wipes for decontaminating high-touch environmental surfaces spiked with EBOV/Mak or VSV is discussed. In summary, removal of EBOV/Mak and VSV using wipes was extensive in this study. In the absence of a sufficient concentration and contact time of an appropriate microbicidal active in DPW (such as the AHP- and QAC-based DPW tested), transfer of a low, albeit significant (from an infectious unit/infectious dose perspective), quantity of infectious virus from the inoculated surface to a secondary surface was observed. In the case of Ebola virus, it is essential that a DPW with an appropriate microbicidal active, following the appropriate contact time, be used to prevent unintended transfer of infectious virus to a clean secondary surface (as observed in negative control /J-Cloth). Otherwise, there exists the possibility of dissemination of Ebola virus and the associated risk of transmission of Ebola virus disease.